EFFECT OF METFORMIN ON URINARY BLADDERCONTRACTION-RELAXATION MECHANISM - AMIN, BADINAN JALAL HAMAD (Fırat Üniveristesi, 2021)
Metformin (Dimethyl-biguanide) is an oral drug used to reduce blood glucose concentrations in patients with non-insulin-dependent diabetes mellitus (NIDDM). In the present study effect of metformin on urinary bladder contraction was investigated. The effect of different concentrations (2mM , 10mM , and 20mM) of metformin on acetylcholine induced contractions of rat bladder strips was tested by using isolated organ bath. In the urinary bladder experiment metformin did not have effect on contraction and relaxation mechanism in the urinary bladder strips. The effects of tested concentrations of metformin (2mM , 10mM , and 20mM) was not statistically significant either on the frequency (p>0.05), the area under contractile curve or peak amplitude of contractions (p>0.05). The results of this study indicate that the antidiabetic drug metformin does not exert any significant effect on the contractile pattern of acetylcholine induced bladder contractions in this in vitro model. Therefore metformin can be used in patients of diabetic mellitus have a problem in urinary bladder because it did not have effect on urinary bladder.

Metformin (Dimetilbiguanid), insüline bağımlı olmayan diabetes mellitus (NIDDM) olan hastalarda kan glukoz konsantrasyonunu düşürmek için oral yoldan uygulanan bir ilaçtır. Bu çalışmada metforminin farklı dozlarının (2mM, 10mM, 20mM) erkek sıçanlarda asetilkolin ile indüklenen kasılmalar üzerindeki etkisi izole organ banyosu kullanılarak test edildi. İdrar kesesi deneyinde metformin mesane şeritlerinde kasılma ve gevşemeye etki etmedi. kasılma sıklığı yukarida belirtilen dozlarda istatistiksel olarak anlamlı değil (p>0.05), Ayrıca alan ve kasılma genliği kullanılan tüm dozlarda istatistiksel olarak anlamlı değildi (p>0.05). Bu çalışmadan elde edilen sonuçlar, antidiyabetik ilaç olan metforminin, in vitro modelde asetilkolinin neden olduğu idrar kesesi kasılmalarının kasılma modeli üzerinde önemli bir etki yapmadığını göstermektedir. Bu nedenle metformin, mesaneye etkisi olmadığı için mesane problemi olan diyabetik mellitus hastalarında kullanılabilir.
Metforminin idrar kesesi kasılması-gevşeme mekanizmasına etkisi
Keywords: Fizyoloji